Sie sind auf Seite 1von 11

# 2018-DSE

MATH EP
M2

## HONG KONG EXAMINATIONS AND ASSESSMENT AUTHORITY

HONG KONG DIPLOMA OF SECONDARY EDUCATION EXAMINATION 2018

## MATHEMATICS Extended Part

Candidate Number
Module 2 (Algebra and Calculus)
Marking Scheme

## 8:30 am – 11:00 am (21/2 hours)

This paper must be answered in English

INSTRUCTIONS

## 1. After the announcement of the start of the examination, you

should ﬁrst write your Candidate Number in the space provided
on Page 1 and stick barcode labels in the spaces provided on Page
1, 3, 5, 7, 9 and 11.

## 3. Attempt ALL questions in this paper. Write your answers in the

spaces provided in this Question-Answer Book. Do not write in
the margins. Answers written in the margins will not be marked.

## 4. Graph paper and supplementary answer sheets will be supplied

on request. Write your Candidate Number, mark the question
number box and stick a barcode label on each sheet, and fasten
them with string INSIDE this book.

## 8. No extra time will be given to candidates for sticking on the

barcode labels or ﬁlling in the question number boxes after the
‘Time is up’ announcement.

Hong Kong Examinations and Assessment Authority
Solution Marks

SECTION A (0 marks)

## 1. f (1 + h) = [(1 + h)2 − 1]e1+h

= (h2 + 2h)e1+h
f (1 + h) − f (1)
f (1) = lim
h→0 h
(h + 2h)e1+h − 0
2
= lim
h→0 h
= lim (h + 2)e1+h
h→0

= 2e

## 2. (x + 3)5 = x 5 + C15 (3)x 4 + C25 (3)2 x 3 + C35 (3)3 x 2 + C45 (3)4 x + 35

= x 5 + 15x 4 + 90x 3 + 270x 2 + 405x + 243
 2  
4 16
(x + 3) x −
5
= (x + 15x + 90x + 270x + 405x + 243) x − 8 + 2
5 4 3 2 2
x x
coeﬃcient of x = (1)(16) + (90)(−8) + (405)(1)
3

= −299

## 3. (a) 2 sin(B − A) = 2 sin B cos A − 2 cos B sin A

= sin A sin B(2 cot A − 2 cot B)
= sin A sin B[cot A + (cot A − 2 cot B)]
= sin A sin B(cot A + (3 − 2) cot B)
= sin A sin B(cot A + cot B)
= sin B cos A + sin A cos B
= sin(A + B)
(b) By (a), the equation is equivalent to
       
4π 5π 5π 4π
sin x + + x+ = 2 sin x + − x+
9 18 18 9
   
13π π
sin 2x + = 2 sin −
18 6
 
1
=2 −
2
= −1
13π 3π
2x + =
18 2

x=
18
∫ ∫
u(5u ) 1
4. (a) u(5u ) du = − 5u du
ln 5 ln 5
u(5u ) 5u
= − +C
ln 5 (ln 5)2

2018-DSE-MATH-EP(M2)-1 1
Solution Marks

## (b) When f (x) = 0,

x(52x ) = 0
x=0
∫ 1
Required area = x(52x ) dx
0
Let u = 2x. Then du
∫ = 2 dx.
1 2
Required area = u(5u ) du
4 0
 2
1 u(5u ) 5u
= −
4 ln 5 (ln 5)2 0
   
1 2(25) 25 1
= − − 0−
4 ln 5 (ln 5)2 (ln 5)2
25 6
= −
2 ln 5 (ln 5)2

## 5. (a) Let u = 1 + x 2 . Then du = 2x dx.

∫ ∫
1
x 1 + x dx =
3 2 x 2 (2x) 1 + x 2 dx
2

1 √
= (u − 1) u du
2

1 3 1
= (u 2 − u 2 ) du
2
5 3
u2 u2
= − +C
5 3
5 3
(1 + x 2 ) 2 (1 + x 2 ) 2
= − +C
5 3

(b) y = 15x 3 1 + x 2 dx

= 15 x 3 1 + x 2 dx
5 3
= 3(1 + x 2 ) 2 − 5(1 + x 2 ) 2 + C
Substitute (0, 2),

2 = 3(1) − 5(1) + C
C=4
5 3
The equation of Γ is y = 3(1 + x 2 ) 2 − 5(1 + x 2 ) 2 + 4.

6. (a) When n = 1,
L.H.S. = (1)(5) = 5
1(2)(15)
R.H.S. = = 5 = L.H.S.
6
The statement is true when n = 1.

r
r(r + 1)(2r + 13)
Assume k(k + 4) = for some r ∈ Z+ .
k=1
6

2018-DSE-MATH-EP(M2)-2 2
Solution Marks

When n = r + 1,

r+1

r
k(k + 4) = k(k + 4) + (r + 1)(r + 5)
k=1 k=1
r(r + 1)(2r + 13)
= + (r + 1)(r + 5)
6
r +1
= [r(2r + 13) + 6(r + 5)]
6
r +1 2
= (2r + 19r + 30)
6
(r + 1)(r + 2)(2r + 15)
=
6
(r + 1)[(r + 1) + 1][2(r + 1) + 13]
=
6
= R.H.S.

## The statement is true when n = k + 1.

By mathematical induction, the statement is true ∀n ∈ Z+ .
555    555

k k +4 1

332
(b) = k(k + 4) − k(k + 4)
k=333
112 223 24 976 k=1 k=1
 
1 (555)(556)(1123) (332)(333)(677)
= −
24 976 6 6
= 1813

7. (a) MX = XM

7 3 a 6a a 6a 7 3
=
−1 5 b c b c −1 5

7a + 3b 42a + 3c 7a − 6a 3a + 30a
=
5b − a 5c − 6a 7b − c 3b + 5c
Comparing corresponding entries,

⎪ 7a + 3b = a

⎨ 42a + 3c = 33a

⎪ 5b − a = 7b − c

⎩ 5c − 6a = 3b + 5c
Solving, we have b = −2a and c = −3a.
 
 a 6a 

(b) det X =  
−2a −3a

= −3a2 + 12a2
= 9a2
Since a  0 or otherwise X is a zero matrix, we have det X  0.
Thus, X is non-singular.

2018-DSE-MATH-EP(M2)-3 3
Solution Marks

−1 1 −3a −6a
(c) X = 2
9a 2a a

1 3 −6
=
9a 2 1
(X T )−1 = (X −1 )T

1 3 2
=
9a −6 1

## 8. (a) f (x) = −A(x 2 − 4x + 7)−2 (2x − 4)

−2A(x − 2)
=
(x 2 − 4x + 7)2
f (x) = −2A(x 2 − 4x + 7)−2 − 2A(x − 2)(−2)(x 2 − 4x + 7)−3 (2x − 4)
= −2A(x 2 − 4x + 7)−3 [(x 2 − 4x + 7) − 2(x − 2)(2x − 4)]
−2A(−3x 2 + 12x − 9)
=
(x 2 − 4x + 7)3
6A(x − 1)(x − 3)
=
(x 2 − 4x + 7)3

When f (x) = 0, we have x = 2.
2A
f (2) = − .
9
Note that A  0 or otherwise f (x) is a zero function. Therefore, f (2)  0.
Thus, f (x) attains its extreme at x = 2.

f (2) = 4
A
=4
22 − 4(2) + 7
A = 12
−24(x − 2)
Thus, f (x) = .
(x 2 − 4x + 7)2
(b) Since (−4)2 − 4(1)(7) = −12 < 0, the equation x 2 − 4x + 7 = 0 has no real solutions.
Therefore, the graph has no vertical asymptotes.
As 0 = deg(12) < deg(x 2 − 4x + 7) = 2, the graph has one horizontal asymptote y = 0 and
no oblique asymptote.
The graph has only one asymptote.
The claim is disagreed.
(c) By (a),
72(x − 1)(x − 3)
f (x) =
(x 2 − 4x + 7)3
When f (x) = 0, x = 1 or 3.
x x<1 1<x<3 x>3
f (x) − + −
f (1) = 3 and f (3) = 3.
Thus, the points of inﬂexions are (1, 3) and (3, 3).

2018-DSE-MATH-EP(M2)-4 4
Solution Marks

SECTION B (0 marks)
1
9. (a) y= ln x
2
dy 1
=
dx 2x
1
Slope of tangent to C at P = .
2r
Slope of normal to C at P = −2r.
Let the coordinates of Q be (q, 0).
0 − 12 ln r
= −2r
q−r
ln r = −4qr + 4r 2
4r 2 + ln r
q=
4r
4r 2 + ln r
The x-coordinate of Q is .
4r
(b) Let the area of PQR be A.
  
1 4r 2 + ln r 1
A= −r ln r
2 4r 2
1 ln r ln r
= · ·
2 4r 2
(ln r)2
=
16r
 
dA 2 1 (ln r)2
= (ln r) −
dr 16r r 16r 2
ln r(2 − ln r)
=
16r 2
dA
When = 0,
dt
ln r(2 − ln r) = 0
ln r = 2 or 0
r = e2 or 1 (rej.)

## r 1 < r < e2 r > e2

dA −
+
dr
A attains its greatest value when r = e2 .
(ln e2 )2
Greatest area =
16e2
1
= 2
4e

2018-DSE-MATH-EP(M2)-5 5
Solution Marks

(c) Let OP = p.

 2
ln r
p= r2 +
2

(ln r)2
= r2 +
4
 − 1  
dp 1 2 (ln r)2 2 ln r dr
= r + 2r +
dt 2 4 2r dt
When r = e,
 − 1  
dp 1 2 1 2 1 dr
= e + 2e +
dt 2 4 2e dt
  − 12  
1 1 1 dr
= · e + 2
e +
2
e 4 4 dt
  12
1 1 dr
= · e2 +
e 4 dt
dp
As ≤ 32e2 ,
dt
 1
1 1 2 dr
· e +
2
≤ 32e2
e 4 dt
 − 1
dr 1 2
≤ 32e e +
3 2
dt 4

dA dA dr
= ·
dt dr dt
ln r(2 − ln r) dr
= ·
16r 2 dt
When r = e,
dA 1 dr
= ·
dt 16e2 dt
 − 1
1 1 2
≤ · 32e e +
3 2
16e2 4
2e
=   12
e2 + 14
2e
< 1
(e2 ) 2
=2

## The claim is correct.

2018-DSE-MATH-EP(M2)-6 6
Solution Marks
∫ ∫
10. (a) (i) sin4 x dx = (sin x) sin3 x dx

= − cos x sin3 x + cos x(3 sin2 x cos x) dx

= − cos x sin3 x + 3 (1 − sin2 x) sin2 x dx
∫ ∫
= − cos x sin3 x + 3 sin2 x dx − 3 sin4 x dx
∫ ∫
4 sin4 x dx = − cos x sin3 x + 3 sin2 x dx
∫ ∫
cos x sin3 x 3
sin x dx = −
4
+ sin2 x dx
4 4
∫ π  π ∫
1 3 π 2
(ii) sin x dx = − cos x sin x +
4 3
sin x dx
0 4 4 0
∫ 0
3 π
=0+ (1 − cos 2x) dx
8 0
 π
3 sin 2x
= x−
8 2 0

=
8
(b) (i) Let u = β − x. Then du = − dx.
∫ β ∫ 0
x f (x) dx = − (β − u) f (β − u) du
0 β
∫ β
= (β − u) f (u) du
0
∫ β ∫ β
= β f (u) du − u f (u) du
0 0
∫ β ∫ β
= β f (x) dx − x f (x) dx
0 0
∫ β ∫ β
2 x f (x) dx = β f (x) dx
0 0
∫ β ∫
β β
x f (x) dx = f (x) dx
0 2 0
(ii) Since sin4 x is continuous on R and sin4 (π − x) = sin4 x, by (b)(i), putting f (x) = sin4 x
and β = π, we have
∫ π ∫
π π 4
x sin x dx =
4
sin x dx
0 2 0
π 3π
= ·
2 8
3π 2
=
16
(c) When y = 0,

x sin2 x = 0
sin x = 0
x=π or 2π

2018-DSE-MATH-EP(M2)-7 7
Solution Marks
∫ 2π

Volume of the solid = π ( x sin2 x)2 dx
π
∫ 2π
=π x sin4 x dx
π
Let u = x − π. Then du = dx.
∫ π
Volume = π (u + π) sin4 (u + π) du
∫0 π
=π (u + π) sin4 u du
∫ π
0
∫ π
=π u sin u du + π
4 2
sin4 u du
0 0
3π 2 3π
=π· + π2 ·
16 8
9π 3
=
16
   
1 a 4(a + 1)  1 a 4a + 4 
   
   
11. (a) (i) (1) 2 a − 1 2(a − 1) = 0 −a − 1 −6a − 10
   
1 −1 −12  0 −a − 1 −4a − 16
1 a 4a + 4
 

= 0 −a − 1 −6a − 10
0 0 2a − 6 
= (1)(−a − 1)(2a − 6)
= 2(a + 1)(a − 3)
(E) has unique solution if and only if 2(a + 1)(a − 3)  0, i.e., a  −1 and a  3.
Thus, the required range is a < −1 or −1 < a < 3 or a > 3.
1 a 4(a + 1) 18 1 a 4a + 4 18
   
 
(2) 2 a − 1 2(a − 1) 20 ∼ 0 −a − 1 −6a − 10 −16 


## 1 −1 −12 b  0 −a − 1 −4a − 16 b − 18

1 a 4a + 4 18
 
∼ 0 −a − 1 −6a − 10 −16 
0 0 2a − 6 b − 2
b−2
Therefore, z = and
2(a − 3)
(−a − 1)y + (−6a − 10)z = −16
−3ab + 22a − 5b − 38
y=
(a − 3)(a + 1)
and

x + ay + (4a + 4)z = 18
a2 b + ab + 10a − 2b − 50
x=
(a − 3)(a + 1)
 
a2 b + ab + 10a − 2b − 50 −3ab + 22a − 5b − 38 b − 2
Thus, (x, y, z) = , ,
(a − 3)(a + 1) (a − 3)(a + 1) 2(a − 3)

2018-DSE-MATH-EP(M2)-8 8
Solution Marks

## (ii) (1) When a = 3, by (a)(i)(2), (E) is equivalent to

1 3 16 18
 
0 −4 −28 −16 

0 0 0 b − 2
If (E) is consistent, then b − 2 = 0, i.e., b = 2.
1 3 16 18 1 3 16 18
   
 
(2) 0 −4 −28 −16  ∼ 0 −4 −28 −16


0 0 0 b − 2 0 0 0 0 
1 3 16 18
 

∼ 0 1 7 4 
0 0 0 0 
1 0 −5 6
 
∼ 0 1 7 4
0 0 0 0
Let z = r, where r ∈ R.
Then x = 6 + 5r and y = 4 − 7r.
Thus, the solutions are {(6 + 5r, 4 − 7r, r) : r ∈ R}.
(b) The ﬁrst three equations are equivalent to (E) at a = 3.
By (a)(ii)(1), the ﬁrst three equations are consistent when s = 2.
By (a)(ii)(2), the solutions are {(6 + 5r, 4 − 7r, r) : r ∈ R}. Substitute it into the forth
equation,

## 2(6 + 5r) − 5(4 − 7r) − 45r = t

t = −8
−−→
12. (a) (i) AB = (−i + 3j − 3k) − (4i − 3j + k) = −5i + 6j − 4k
−−→
AC = 3i + 2j + 4k
 
 i j k
−−→ −−→  

AB × AC = −5 6 −4
 
3 2 4

## = (24 + 8)i − (−20 + 12)j + (−10 − 18)k

= 32i + 8j − 28k
−−→ −−→ −−→
(ii) ( AB × AC) · AD = (32i + 8j − 28k) · (−i + j − 6k)
= −32 + 8 + 168
= 144
1 −−→ −−→ −−→
Volume = |( AB × AC) · AD|
6
144
=
6
= 24

2018-DSE-MATH-EP(M2)-9 9
Solution Marks
−−→ −−→
(iii) Let n = AB × AC.
−−→
−−→ DA · n
DE = (n)
n·n
−−→ −−→
−( AB × AC) · AD
= (n)
n·n
−144
= 2 (32i + 8j − 28k)
32 + 82 + 282
4
= (−8i − 2j + 7k)
13
−−→ −−→
−−→ BD · BC −−→
(b) (i) BF = −−→ −−→ ( BC)
BC · BC
(4i − 5j − 2k) · (8i − 4j + 8k)
= (8i − 4j + 8k)
82 + 42 + 82
= 2i − j + 2k
−−→ −−→ −−→
DF = BF − BD
= −2i + 4j + 4k
−−→ −−→ −−→
(ii) E F = DF − DE
1
= (i + 10j + 4k)
13
−−→ −−→ 1
E F · BC = (i + 10j + 4k) · (8i − 4j + 8k)
13
=0
−−→ −−→
Thus, BC ⊥ E F.
(c) Note that BC is the line of intersection of two planes, DF ⊥ BC and E F ⊥ BC.
The angle required is equal to ∠DFE.
−−→ −−→
DF · E F = (DF)(E F) cos ∠DFE
  √
1 12 + 102 + 42
(−2i + 4j + 4k) · (i + 10j + 4k) = 2 + 4 + 4 ·
2 2 2 cos ∠DFE
13 13

54 = 6 · 3 13 cos ∠DFE

3 13
cos ∠DFE =
13

3 13
∠DFE = cos−1
13

3 13
The required angle is cos−1 .
13

END OF PAPER

2018-DSE-MATH-EP(M2)-10 10